Match exposure, consecutive match number, and recovery days affect match running during international women's soccer tournaments - Brown, G. A.; Massard, T.; Wignell, T.; McCall, A.; Duffield, R. (The Journal of Strength and Conditioning Research, 2024)
To determine the influence of tournament-specific factors (match exposure, consecutive matches, and days between matches) on match running in women's international soccer players (footballers), 28 players from 1 national team were observed over 4 international tournaments using 10 Hz global positioning system units. Linear mixed models with a forward selection approach were used to analyze the collective effect of tournament-specific factors of match exposure (playing time), consecutive matches (count), days between matches (count) and time on pitch on relative (min-1) match running metrics (total distance, high-speed running, very high-speed running, accelerations, and decelerations), and the change in these metrics between halves. The significance level was set at p < 0.05. Days between matches were included in the final models for total distance (p < 0.0001), high-speed running (p = 0.002), very high-speed running (p = 0.025), and change in accelerations (p < 0.0001) and decelerations (p = 0.002). Prior match exposure was included in the models for total distance (p = 0.021), change in total distance (p < 0.0001), and change in high-speed running (p = 0.0008). Consecutive match number was included in the model for deceleration (p = 0.030), change in very high-speed running (p = 0.016), change in acceleration (p < 0.0001), and change in deceleration (p < 0.0001). Time on pitch was included in the final total distance (p = 0.044), high-speed running (p < 0.0001), acceleration (p < 0.0001), and deceleration (p = 0.0003) models. Overall, reduced match running throughout tournaments was associated with increased time on pitch and =3 days between matches. Increasing match exposure and more time between matches minimizes reductions in match running between halves. Practitioners can use these variables to inform player monitoring during international soccer tournaments and on return to clubs.